Germany and the UK: Perspectives for deepening the bilateral dialogue on development policy - Niels Keijzer; Ina Friesen (Deutsches Institut für Entwicklungspolitik (DIE), 2022)
Germany and the United Kingdom of Great Britain and Northern Ireland (UK) are the second- and fourth-largest providers of official development assistance (ODA) worldwide and are key actors in driving international policy discussions on global development in the Organisation for Economic Co-operation and Development (OECD), the G7, the G20 and other key groupings and platforms. The development policies of both countries witnessed important convergence and detailed cooperation during the first decade of this millennium - a period when Western countries understood development cooperation as a source of considerable soft power, which was demonstrated in rising budgets and like-minded policy directions. The austerity policies that followed the global economic and financial crisis, and the UK's decision to leave the European Union (EU) in 2016, have challenged the bilateral relationship in the development policy area between Germany and the UK. The UK's departure from the EU has reduced the number of joint interactions and corresponding opportunities for identifying cooperation initiatives. Halfway through the period envisaged for the completion of the 2030 Agenda, both countries are adjusting their development policies, seeking to determine their future European roles and global development ambitions, but they remain key partners in global development. Both the UK and Germany have recently revised or are in the process of preparing development policy strategies as part of their integrated foreign policies - a reflection process which in recent months has been challenged to adjust to the implications of the war in Ukraine. The case remains strong for regular exchanges and cooperation on development policy between both countries, including by intensifying dialogues and resuming formal secondments between the FCDO and the German Federal Ministry for Economic Cooperation and Development (BMZ). Two areas in particular offer good prospects. First of all, the UK and Germany should closely work together to deliver on the current G7 Presidency agenda - including the key focus on infrastructure investment, as initiated during last year's UK Presidency. Other key opportunities for cooperation include gender and climate action, as well as the provision of global public goods. Secondly, Germany and the UK should seek to engage in and harness the role of the OECD as a provider of key standards for international development policy and as an important forum for peer learning. As key providers of global development finance, the legitimacy of its reporting system is essential to both countries' influence and contribution to global development.
Keywords: 330